Pengaruh Gaya Kepemimpinan Dan Lingkungan Kerja Terhadap Kinerja Karyawan Dengan Motivasi Kerja Sebagai Variabel Intervening Pada PT. Tangerang Gas Industri - Putri Tasya Tasya; Andiana Rosid; Slamet Tedy Siswoyo (Jurnal Manajemen DIVERSIFIKASI, 2025)
Based on data on the performance of company employees at PT. Tangerang Gas Industri, it has not met the target of good performance according to company standards. Employee performance can be improved if the company is led by a suitable leadership style and can create a conducive work atmosphere for employees. This study aims to determine the effect of leadership style on employee performance, to determine the effect of work environment on employee performance, to determine work motivation in intervening leadership style on employee performance, to determine work motivation in intervening work environment on employee performance. The sample in this study were employees of PT. Tangerang Gas Industri as many as 36 employees. Data collection using a questionnaire, and data analysis using Validity Test, Reliability Test, Normality Test, Homogeneity Test, Linearity Test and Regression Significance, and Substructural Path Analysis with the program (SPSS 20). The results of this study indicate that there is a direct influence of Leadership Style and Work Environment on employee performance, there is a direct influence of Leadership Style and Work Environment on employee work motivation, and there is a direct influence of employee performance on work motivation of PT Tangerang Gas Industri.